Characterization of Mughal Bricks from Jahangir Tomb, Lahore-Pakistan - Gulzar, S.; Chaudhry, M.N.; Burg, J.P.; Saeed, S.A. (Asian Journal of Chemistry, 2013)
Jahangir tomb, which was constructed during the Mughal era in the subcontinent, is one of the remarkable monuments in the city of Lahore, Pakistan. This particular tomb is representative of Mughal tomb architecture followed by the Persian traditions. In this study, the brick samples were studied employing chemical, mineralogical and micro-structural techniques (X-ray florescence, optical microscopy, SEM-EDS and X-ray diffraction) to determine their characteristics which in turn will help formulate the future conservation strategy for compatible materials. The Mughal bricks showed high content of SiO2 (60-70 %), Al2O3 (14-16 %) and Fe2O3 (5.5-7.5 %) with low amounts of Na2O (1-1.5 %), K2O (3-3.5 %), MgO (2.3 %) and CaO (2-2.5 %). The bricks also showed low density, high porosity and were produced from raw materials containing calcium poor clays fired at low temperatures. New bricks to be used in restoration works of this tomb should be chemically and physically compatible with the existing masonry. New bricks must therefore be produced by using Ca-poor clays with compatible chemical characteristics, traditional production techniques and heating at low temperatures (ca. 850 ºC).